Moderasi Kualitas Laporan Keuangan pada Kemandirian, Ketergantungan, Belanja Modal terhadap Kinerja Daerah - Rahmadhanty, Dwi Riski; Firmansyah, Amrie (Penerbit Goodwood, 2025)
Purpose: This study aims to provide robust statistical evidence on the impact of regional government independence, dependency on central government funding, and capital expenditure on the financial performance of regional governments in South Sumatra Province from 2007 to 2021. Methodology: The study utilizes secondary data from financial reports of district and city governments in South Sumatra for the period 2007-2021, obtained through the official websites of the Supreme Audit Agency (BPK) and the Directorate General of Fiscal Balance. Results: The findings reveal that regional government independence, central government dependency, and capital expenditure individually have a negative impact on the financial performance of South Sumatra's regional governments. Moderation analysis shows that high-quality financial reporting strengthens the positive impact of regional independence and dependency on financial performance, suggesting that accurate and transparent reporting may help maximize the benefits of fiscal autonomy and central transfers. Limitations: This study is limited to secondary data from financial reports, which may not capture all factors affecting regional financial performance. Additionally, the focus on district and city governments in South Sumatra may limit the generalizability of the findings to other regions. Contribution: This study offers a valuable reference for optimizing regional financial strategies to enhance fiscal autonomy and efficiency in local governments.